Pengaruh Promosi dan Keunggulan Produk Terhadap Peningkatan Jumlah Nasabah Gadai Emas (Rahn) Pada PT. Bank Aceh Syariah Cabang Jeuram Nagam Raya - Nirlia Okta Wirda; Israk Ahmadsyah; Evriyenni Evriyenni (Jurnal Ekonomi Regional Unimal, 2021)
This study aims to determine the effect of promotion and product excellence on increase in the number of gold pawn customers (rahn) at PT. Bank Aceh Syariah Jeuram Nagan Raya Branch. This research method uses quantitative methods with data collection techniques through distributing questionnaires to 90 respondents, namely gold pawn customers (rahn) PT. Bank Aceh Syariah Jeuram Nagan Raya Branch. The partial test results show that the promotion variable has no effect on increasing the number of gold pawning customers (rahn). While the product excellence variable has an effect on increasing the number of gold pawn customers (rahn). Furthermore, the results of the simultaneous test show that the promotion and product excellence variables together have a significant effect on increasing the number of gold pawning customers (rahn) at PT. Bank Aceh Syariah Nagan Raya Branch.